2007
DOI: 10.1504/ijlsm.2007.012995
|View full text |Cite
|
Sign up to set email alerts
|

Integrating supply chain operations in the internet era

Abstract: The internet's potential impact on supply chain operations is often approached in the literature in a quite generic way due to the complex nature of supply chains and the different levels of operations' integration. Drawing on existing research, this paper proposes an overall framework of supply chain integration and then attempts to provide a categorisation of the internet's role in the supply chain activities, providing insights from various sectors. The purpose of this paper is to describe and present the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For successful implementation of SSCM, suppliers must become environmentally and socially responsible (Zhu et al , 2005). Several researchers have identified the need to evaluate the depth of collaborative relationships in SSCM context (Matopoulos et al , 2007). However, it has been found that there is very little research done that analyzes the depth of collaboration like understanding power imbalances in the SC (Hoejmose and Adrien-Kirby, 2012; Walker and Jones, 2012).…”
Section: Perspectives Of Sscmmentioning
confidence: 99%
“…For successful implementation of SSCM, suppliers must become environmentally and socially responsible (Zhu et al , 2005). Several researchers have identified the need to evaluate the depth of collaborative relationships in SSCM context (Matopoulos et al , 2007). However, it has been found that there is very little research done that analyzes the depth of collaboration like understanding power imbalances in the SC (Hoejmose and Adrien-Kirby, 2012; Walker and Jones, 2012).…”
Section: Perspectives Of Sscmmentioning
confidence: 99%
“…Olhager and Selldin (2003) provide evidence on Swedish companies of a focused use of IT tools on specific supply chain activities. Matapoulos et al (2007) show that the impact of internet based tools on supply chains changes significantly among different industrial sectors. Among all these contributions, Cagliano et al (2003) provide important evidence based on the IMSS III questionnaire, collected in 2001, regarding how companies are shaping their supply chain through the internet.…”
Section: The Diffusion Of the Internet As A Sc Integration Meanmentioning
confidence: 99%
“…Several authors claim that exchanges and supply chain integration by means of internet based tools is increasing (Bertelè et al, 2005;Forrester Research, 1999;Lee and Barua, 1999;Boyer and Olson, 2002;Zhu and Kraemer, 2002;Barua et al, 2004). Literature assumes that after the "peak of inflated expectation" was reached, the adoption of information technologies proceeds firmly (Cagliano et al, 2005) even if it may change between different countries (Kemppaien and Vepsalainen, 2003;Olhager and Selldin,2003) and different industrial sectors (Matapoulos et al, 2007). Given the previous contributions we formulate the following proposition: P1: The level of adoption of internet based tools within supply chain relationships has increased over time Literature suggests that the impact of the different tools depend from several contingent factors such as the existence of specific kinds of teams (Giunipero and Vogt, 1997;Robey et al, 2002;Johnson et al, 2007), the possibility of developing specific forms of cooperation along the supply chain (Sanders, 2007;Devaraj et al, 2007), companies competences and organizational structures (Power and Singh, 2007).…”
Section: Research Goals and Hypothesismentioning
confidence: 99%
“…In last decade, an increasing attention has been devoted to the phenomenon and to its deleterious consequences. Several issues have been investigated within the BE and supply chain field such as: reverse logistic (Zhou and Disney, 2006), multi-product (Reichhart et al, 2008), stochastic lead times (Boute et al, 2007), capacity constraints (Yuan and Ashayeri, 2009), flexibility (Jain et al, 2009;Hanna et al, 2010), batching (Potter and Disney, 2006;Hussain and Drake, 2011), collaboration (Matopoulos et al, 2007;Darwish and Goyal 2011;Sujatha, 2011), order policies (Azadeh et al, 2011;Cannella et al, 2011), pricing (O'Donnell et al, 2009), and performance measurement (Wong and Wong, 2008;Keebler and Plank 2009;Pettersson and Segerstedt, 2011) amongst others. Analogously, several studies have addressed the methodological approaches to study the dynamics of supply chains (Riddalls et al, 2000;Kleijnen and Smits, 2003;Dejonckheere et al, 2004;Holweg and Disney, 2005;Geary et al, 2006;Lemmens, 2006, Towill et al, 2007;Disney and Lambrecht, 2008;Nilakantan, 2010;Ciancimino and Cannella, 2011;Lättilä, 2011;Scholz-Reiter et al, 2011).…”
Section: Supply Chain Dynamics: Research Methodologies and Desmentioning
confidence: 99%